Revisiting mental accounting: the dominance of power prestige over personality, retention time, and qana’ah in shaping consumptive behavior - Juniaty Ismail; Sri Apriyanti Husain; Setia Ningsih; Nur Zaimah Ubaidillah (Universitas Islam Negeri Walisongo Semarang, 2026)
Purpose - This study aims to examine the influence of various financial psychological constructs and spirituality on the consumptive behavior of accounting students at five universities in Gorontalo, focusing on the moderating role of mental accounting. Method - The research employed a quantitative approach using Partial Least Squares-Structural Equation Modeling (PLS-SEM) and involved 156 accounting students as respondents. Result - The results indicate that power prestige has a significant positive effect on consumptive behavior, while retention time, personality type, and qana’ah do not show significant effects. Mental accounting acts as a moderator that strengthens the relationship between power prestige and consumptive behavior, although its influence is not significant on other variables. This study confirms that students’ consumptive behavior is more influenced by social status than by personality traits, time management, or spiritual values. Implication - The implications of this research highlight the need for financial education that not only focuses on rational financial management but also raises awareness of the social impact of financial decision-making. Originality - This study makes a significant contribution to the behavioral finance literature by highlighting the interplay between social, psychological, and spiritual factors in shaping students' consumptive behavior.